Psychosocial Impact of Cleft Lip and Palate Children on Their Parents - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Aim:To analyze the psychosocial impact of orofacial cleft child on the parents in Kano, North Western Nigeria.Material and Methods:We interviewed 150 parents of patients with orofacial clefts using Interviewer Administered Questionnaire (IAQ) from June to December 2012 for mood state, family stress coping strategy, and impact of cleft on parents using POMS-SF, FSCQ, PICP-Q questionnaire, respectively.Results:Age range of parents was 15–65 years (F: M = 7.3:1); the parents in the 2nddecade formed the largest group (44.7%) followed by the parents in the 3rddecade (36.7%). Following POMS-SF rating, 89.3% of the respondent had good mood, 3.3% had fair mood, while 7.3% had poor mood. Most of the parents (97.3%) were able to cope with the stress of caring for a cleft child. Stress among the parents of children having bilateral cleft was higher than unilateral cleft but not statistically significant. Also, the stress felt by the parents having children with severe cleft was higher than mild-moderate cleft though not statistically significant. The mood state of the parent that had children with either unilateral or bilateral clefts were similar, while there was no statistically significant difference in the mood of parents of children that had mild-moderate or severe cleft.Conclusion:Through this study, we corroborated that the psychosocial impact of orofacial cleft is not easy to define and quantify. The most important concern among the parents in all these categories was surgical correction for their wards.